Controlled Metric Space and Fixed Point Theorems for Jaggi–Suzuki–Type Hybrid Contraction - Swati Parashar; Manoj Kumar; Pankaj Kumar; Rahul Shukla (International Journal of Mathematics and Mathematical Sciences)
In this paper, we introduce a new notion of generalized Jaggi–Suzuki–type hybrid contraction in the setting of controlled metric space and prove some fixed point theorems by making use of the same. A suitable example is also provided to prove the validity of our results. As an application, a fractional differential equation with singular kernels is solved by making use of our result.